Comparison of wild and introduced Dracocephalum jacutense P.: Significant differences of multicomponent composition - Razgonova, Mayya P.; Okhlopkova, Zhanna M.; Rozhina, Zoya G.; Egorova, Polina S.; Ercisli, Sezai; Golokhvast, Kirill S. (Horticulturae)
Dracocephalum jacutense is endemic to eastern Siberia of Russia and is accepted in the rare and endangered category. The plant was first collected by K.S. Baikov in 1985 in the vicinity of the village Sangar (Kobyaysky district, Yakutia) and then described by G.A. Peshkova in Flora of Siberia in 1997. D. jacutense has been introduced in the Botanical Garden of Yakutia since 2009. The aim of this work is to conduct a comparative analysis of the chemical composition of aerial parts (leaves, inflorescences, stems) of D. jacutense Peschkova collected both in controlled conditions (the Botanical Garden of Yakutia) and in a natural-grown area (the vicinity of the village of Sangar, Kobyaysky district of Yakutia). A total of 156 bioactive compounds were successfully characterized in extracts of D. jacutense based on their accurate MS (Mass Spectrometry) fragment ions by searching online databases and the reported literature. The detailed study of the composition by tandem mass spectrometry revealed a significant difference in the polyphenol composition of the samples. Wild-grown plant samples had a higher number of polyphenolic compounds (92 compounds) than plant samples grown in the Botanical Garden (56 compounds), which were not previously described in the genus Dracocephalum. In addition, a total of 37 compounds of other chemical groups were identified that were not previously identified in the genus Dracocephalum. In general, the extract of D. jacutense, which was grown in wild conditions, was found to be a richer source of flavones, flavanols, flavan-3-ols, phenolic acids, and anthocyanidins compared to plants grown in controlled conditions in the Botanical Garden. Our results build on the current understanding of the biochemical richness of wild-grown samples over controlled-grown ones and preserve a rare and endangered D. jacutense in the flora of Yakutia. We proposed to be preserved on the basis of the development of an in vitro micropropagation protocol in our lab in the near future.